How (Not) to Foster Innovations in Public Infrastructure Projects - Eva I. Hoppe; Patrick W. Schmitz (The Scandinavian Journal of Economics, 2021)
The government wants an infrastructure-based public service to be provided. First, the infrastructure has to be built; subsequently, it has to be operated. Should the government bundle the building and operating tasks in a public–private partnership? Or should it choose traditional procurement (i.e., delegate the tasks to different firms)? Each task entails unobservable investments to come up with innovations. It turns out that, depending on the nature of the innovations, bundling can either stimulate or discourage investments. Moreover, we find that if renegotiation cannot be prevented, public–private partnerships might lead the government to deliberately opt for technologically inferior projects.
Keywords: 330; Contract theory; moral hazard; procurement; public–private partnerships; renegotiation